RNA polymerase II clusters form in line with surface condensation on regulatory chromatin - Pancholi, Agnieszka; Klingberg, Tim Georg; Zhang, Weichun; Prizak, Roshan; Mamontova, Irina; Noa, Amra; Sobucki, Marcel; Kobitski, Andrei Yu; Nienhaus, Gerd Ulrich; Zaburdaev, Vasily; Hilbert, Lennart (Molecular Systems Biology, 2021)
It is essential for cells to control which genes are transcribed into RNA. In eukaryotes, two major control points are recruitment of RNA polymerase II (Pol II) into a paused state, and subsequent pause release toward transcription. Pol II recruitment and pause release occur in association with macromolecular clusters, which were proposed to be formed by a liquid–liquid phase separation mechanism. How such a phase separation mechanism relates to the interaction of Pol II with DNA during recruitment and transcription, however, remains poorly understood. Here, we use live and super-resolution microscopy in zebrafish embryos to reveal Pol II clusters with a large variety of shapes, which can be explained by a theoretical model in which regulatory chromatin regions provide surfaces for liquid-phase condensation at concentrations that are too low for canonical liquid–liquid phase separation. Model simulations and chemical perturbation experiments indicate that recruited Pol II contributes to the formation of these surface-associated condensates, whereas elongating Pol II is excluded from these condensates and thereby drives their unfolding.
CRIS-Team Scopus Importer:2021-10-08
Keywords: active matter; gene regulation; nuclear organization; super-resolution microscopy; transcriptional condensates